Risk Assessment Method for Cable System Construction of Long-Span Suspension Bridge Based on Cloud Model - Zhifang Lu; Chaofan Wei; Muyu Liu; Xiaoguang Deng (Advances in Civil Engineering)
Cable system construction is one of the most risky construction stages of long-span suspension bridges, and a reliable risk assessment is an important means to ensure the construction safety. This study proposes a risk assessment method for cable system construction of suspension bridges based on the cloud model, which can combine randomness and fuzziness of risk information effectively. First, a multilevel evaluation index system is built by disassembling the process of cable system construction. Next, the index weights are calculated by the uncertain analytic hierarchy process (AHP). Then, according to the cloud model, a risk assessment model for cable system construction of the suspension bridge is established by realizing the mutual transformation between qualitative language and quantified data. Finally, an illustrative example concerning the risk of cable system construction of Wuhan Yang-Si-Gang Yangtze River Bridge is provided to demonstrate the feasibility and objectivity of the proposed method.